1977
DOI: 10.2337/diab.26.12.1147
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Neuropathy and Painless Myocardial Infarction in Diabetic Patients: Histologic Evidence of Their Relationship

Abstract: Myocardial infarction is considered the prime cause of death among adult diabetic patients. In a great number of cases, during myocardial infarction the patients don't feel pain or it is atypical. Diagnosis can be neglected, and mortality increases. In search of an explanation for the absence of pain in these patients, the authors studied the autonomic nerve fibers of the heart muscle with argentic and combined techniques, looking for lesions in the sympathetic or parasympathetic nerve fibers that conduct pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(21 citation statements)
references
References 0 publications
2
17
0
1
Order By: Relevance
“…Several explanations are possible (including a different threshold of pain sensitivity or psychological denial) but cardiac autonomic neuropathy almost certainly plays an important role, potentially involving dysfunction at varying levels – from the pain receptors, afferent neurons or gating mechanisms to the supratentorial translation of ischaemia into pain. Many years ago, an autopsy study in a diabetic patient who had silent infarction found pathologic changes in cardiac afferent neurons consistent with a neuropathy (4), and the prolonged anginal threshold reported in patients with DM has been found to occur in association with reduced heart rate variability (5), an early sign of cardiac autonomic nerve dysfunction (CAN). The failure to develop angina at the onset of ischaemia will have a permissive effect on the diabetic subjects' exercise tolerance: they are able to exercise longer in the absence of chest pain and at risk of developing more severe ischaemia as a result.…”
Section: Discussionmentioning
confidence: 99%
“…Several explanations are possible (including a different threshold of pain sensitivity or psychological denial) but cardiac autonomic neuropathy almost certainly plays an important role, potentially involving dysfunction at varying levels – from the pain receptors, afferent neurons or gating mechanisms to the supratentorial translation of ischaemia into pain. Many years ago, an autopsy study in a diabetic patient who had silent infarction found pathologic changes in cardiac afferent neurons consistent with a neuropathy (4), and the prolonged anginal threshold reported in patients with DM has been found to occur in association with reduced heart rate variability (5), an early sign of cardiac autonomic nerve dysfunction (CAN). The failure to develop angina at the onset of ischaemia will have a permissive effect on the diabetic subjects' exercise tolerance: they are able to exercise longer in the absence of chest pain and at risk of developing more severe ischaemia as a result.…”
Section: Discussionmentioning
confidence: 99%
“…34 Cardiac sensory nerve impairment causes silent myocardial ischemia and this is a likely a major cause of sudden death in DM patients. 35 Further, there is data which indicates nerve sprouting induced by a potent stimulator of NGF after myocardial injury increases the incidence of ventricular tachyarrhythmias. 36 …”
Section: Pathophysiologymentioning
confidence: 99%
“…However, NGF also plays a role in the development of sensory innervation, and afferents responsible for the transduction of stimuli such as hypoxia, acidosis and pain during myocardial ischaemia (Hua et al, 2004). Sensory innervation has been shown to be impaired in conditions such as diabetes mellitus and may contribute to the phenomenon of silent myocardial ischaemia and the genesis of malignant ventricular arrhythmia (Faerman et al, 1977). Direct gene transfer of NGF into diabetic rat hearts improved cardiac sensory innervation (Ieda et al, 2006) and recombinant NGF has been shown to be safe when administered to diabetic patients with polyneuropathy (Apfel et al, 2000).…”
Section: Efferent Cardiac Sympathetic Neurotransmission In Health Andmentioning
confidence: 99%